Achieving Quality Integrated Care for Adolescent Depression: A Scoping Review - Diana Sarakbi; Dianne Groll; Joan Tranmer; Kim Sears (SAGE Publishing, 2022)
Introduction: While primary care is often the first point of contact for adolescents with depression, more than half of depressed adolescents are either untreated or undertreated. A scoping review had been completed to summarize approaches for achieving quality integrated care in primary care focused on adolescent depression. Methods: The scoping review followed the methodological framework for scoping studies from Arksey and O'Malley. Articles were grouped into themes and mapped to 6 quality domains for integrated care from the practice integration profile survey and 3 levels of stakeholders based on WHO's definition for health systems (patient/family, primary care team, and national/sub-national health system). Results: A total of 868 records were screened resulting in 22 articles at the patient/family-level (5/22), the primary care team-level (18/22), and the national/sub-national health system-level (16/22). The results highlighted multilevel approaches to support the delivery of quality integrated care for adolescent depression in primary care: (1) population-focused using patient registries, routine screening based on standardized algorithms, and patient-centered strategies, (2) team-driven where primary care clinicians collaborate with mental health clinicians as part of a primary care team, (3) evidence-based delivery of mental health services across the integrated care pathway from screening to follow-up visits, and (4) measurement-guided by leveraging the electronic health record infrastructure to learn from patient outcomes. Conclusion: More research is needed on how to provide quality integrated care for adolescent depression, specifically on patient engagement and retention, grounded in the frontline experiences of patients, families, and clinicians and supported by national and/or sub-national guidelines. A learning system could help integrate mental health services in primary care in a way that is consistent across the national and/or sub-national health system.